Towards sustainable development in China: How do green technology innovation and resource misallocation affect carbon emission performance? - Du, Mingyue; Zhou, Qingjie; Zhang, Yunlai; Li, Feifei (Frontiers in Psychology, 2022)
Green technology innovation is an effective way to achieve carbon neutrality and sustainable development. Based on the provincial panel data of 30 provinces in China from 2005 to 2018, this paper examines the relationship between green technology innovation, resource misallocation and carbon emission performance by constructing panel regression models and the dynamic threshold panel model. The research results show that green technology innovation significantly improves carbon emission performance. Further analysis shows that both capital misallocation and labor misallocation have a negative impact on carbon emissions performance. Furthermore, capital misallocation and labor misallocation hinder the contribution of green technology innovation to improving carbon emissions performance. The regression results of the threshold model show that there exists a threshold effect of green technology innovation on carbon emission performance. As the degree of resource misallocation increases, the positive impact of green technology innovation on carbon emissions performance gradually decreases. This research provides an important reference for the policy implementation to optimize resource allocation and improve the environmental effects of green innovation.